(untitled) (Medico Legal Update, 2021)
Background: Periodontal disease is one of the most common diseases in the oral cavity that may be influenced by the blood grouping system among individuals. The purpose of this study was to determine whether there was an association between radiographic findings and ABO blood groups in patients with periodontal diseases. Material and Method: A prospective study carried out on 200 subjects (99) male and (101) female, aged (18 to 65) who diagnosed clinically with periodontitis who were requested for panoramic and were asked for ABO blood group and Rh factor determination. The subjects were divided into two groups according to these findings, as those with (localized chronic periodontitis) and (generalized chronic periodontitis). The association between blood groups and periodontal health were investigated. Result: There is more predominance of the localized chronic periodontitis (60%) of subjects. The distribution periodontitis with different blood group of the study population (41%, 30%, 20% and, 9%)of blood group O followed by B, A, AB respectively. There is more predominance of subjects with Rh positive group (86.5%) The association between ABO and Rh with age groups and with gender were found to be statistically not significant, whilethe association between both localized and generalized chronic periodontitis and Rh factor was a significant. Conclusion: The association between periodontal diseases and blood group show the high risk people to determine a perfect treatment plan strategy.